Anteseden yang Mempengaruhi Kinerja Guru: Work Engagement, Kepuasan Kerja, dan Komitmen Organisasi [Antecedents Affecting Teacher's Performance: Work Engagement, Job Satisfaction, and Organizational Commitment] - Octavianus Octavianus (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2022)
Performance has become an essential concern of an organization. An employee who performs well will be able to encourage growth within and outside the organization, so that job performance evaluation is the organization's ultimate goal to ensure that all employees have fulfilled their duties and responsibilities. This study aimed to analyze the effect of organizational commitment, job satisfaction, and work engagement on the performance of XYZ School teachers. It is because performance is an essential key for the XYZ School management team to maintain all students' and parents' reputation and trust in general. Data were collected through survey using questionnaire from 86 teachers from XYZ School. The research approach used is quantitative with the PLS-SEM method assisted by SmartPLS 3.2.7 software that evaluates the inner and outer models. The results showed that work engagement and organizational commitment positively affect performance, while job satisfaction has a negative effect on performance.